Analisis Kinerja Perusahaan Sebelum dan Sesudah Merger dan Akuisisi (Studi Empiris pada Perusahaan Non-Keuangan yang Terdaftar di Bursa Efek Indonesia Tahun 2009-2017) - Cecilia Chandra Halim; Indra Widjaja (Universitas Tarumanagara, 2020)
It is undeniable that the world is moving towards to an era of mergers and acquisitions (M&A). M&A that emerged in Asia began with a change in policy after the economic crisis. In the period of 2012 - 2015, based on reports from McKinsey and Reuters showed an increase in the value of mergers and acquisitions in Indonesia amounted to 16.7%, which at the same time M&A in the Asia Pacific and the world experienced a decline. The purpose of this study is to analyze the Companies performance that conduct M&A both in terms of financial and market value. The samples in this study consisted of 16 non-financial companies listed on the Indonesia Stock Exchange in the period 2009-2017. Financial performance will be measured using financial ratios and market performance will be measured using Tobin's Q ratio. The results of this study indicate that it takes a long time to show that there is a synergy between companies conducting mergers and acquisitions.